Komunikasi Interpersonal Termediasi Instagram Live dalam Upaya Resolusi Konflik - Indreswari, Esfandani Peni (Lembaga Pengembangan Kinerja Dosen, 2024)
Technological developments have changed the way humans handle conflict. Face-to-face communication has become the least used method of conflict resolution. Nowadays, conflict resolution is established through mediated communication, one of which is the social media Instagram. This research uses a qualitative approach and attempts to explain the role of Instagram in mediating interpersonal communication processes to resolve conflicts related to gender issues. @poppyrahardjo's Instagram Live session was used as a corpus in this research. The research results show that interpersonal communication mediated by Instagram Live can provide space for communicators to open up and establish a similar perception of their opinions on gender issues. There are three stages to establishing a similar perception, discourse development, openness process, and perception equality process.